Hematocrit and incidence of venous thromboembolism - Folsom, Aaron R. (Res Pract Thromb Haemost, 2020)
BACKGROUND: Patients with polycythemia vera with high hematocrit have increased risk of venous thromboembolism (VTE). OBJECTIVE: To determine whether high hematocrit in the general population is also associated with elevated VTE risk. METHODS: The prospective Atherosclerosis Risk in Communities Study performed a complete blood count in 13 891 adults aged 45 to 64 in 1987 to 1989. We identified incident hospitalized VTEs through 2015 and performed proportional hazards regression analyses using race‐sex–specific categorization of hematocrit percentiles (ie, <5th, 5th to <25th, 25th to <75th, 75th to <95th, and 95th‐100th percentiles, with the 25th to <75th percentile serving as the reference). RESULTS: Over a median follow‐up of 26 years, 800 participants had an incident venous thrombosis of the leg and/or a pulmonary embolism. There was a nonlinear association of hematocrit with VTE incidence, with risk elevated 72% for participants above the 95th percentile of hematocrit compared with the reference. Specifically, hazard ratios (95% confidence intervals) of incident VTE were 1.27 (0.91‐1.76), 1.06 (0.87‐1.28), 1 (reference), 1.17 (0.98‐1.40) and 1.72 (1.30‐2.27) across the 5 hematocrit percentiles, adjusted for age, race, sex, body mass index, smoking status and pack‐years, and other confounding variables. The association of high hematocrit with VTE was limited to provoked VTE, with little evidence for unprovoked VTE. Hemoglobin above the 95th percentile also was associated with an increased risk of VTE. In contrast, there were no significant associations of platelet, leukocyte, neutrophil, or lymphocyte counts with VTE incidence. CONCLUSION: High hematocrit and hemoglobin in a general middle‐aged population sample were associated with increased long‐term risk of VTE, particularly provoked VTE.